2007
DOI: 10.1007/s11104-007-9276-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of partial root drying and patchy fertilizer placement on nutrient acquisition and growth of oilseed rape

Abstract: Partial rootzone drying (PRD) is widely investigated as an effective irrigation technique, resulting in higher water use efficiency and yield for plants growing under mild water deficit. Nutrition is another important factor affecting plant yield, but nutrient acquisition has only rarely been considered in conjunction with PRD. Here we investigate the interaction between water and fertilizer supply in a pot experiment with oilseed rape (Brassica napus L.). Eight treatments were set up for the experiment, a fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Thus, NO 3 -N in 40-60 cm under NP might become an ideal N source for absorption when plants are in dire need of N nutrition. This compares well with the findings that the enhanced decrease of NO 3 -N in local area was closely related to the improved root growth (Wang, de Kroon, & Smits, 2007). These suggested that dynamics of soil NO 3 -N were related to the supply of N and water, crop N requirement and the root growth.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, NO 3 -N in 40-60 cm under NP might become an ideal N source for absorption when plants are in dire need of N nutrition. This compares well with the findings that the enhanced decrease of NO 3 -N in local area was closely related to the improved root growth (Wang, de Kroon, & Smits, 2007). These suggested that dynamics of soil NO 3 -N were related to the supply of N and water, crop N requirement and the root growth.…”
Section: Discussionsupporting
confidence: 88%
“…Another conspicuous feature from our measurements of SWC in both experiments is that dry roots occasionally develop in all treatments, not only when partial root-zone drying is induced (see also Wang et al 2007). In our Phytotron plants grew under nearambient conditions, and our water regimes reflected current crop practices under partial root-zone drying.…”
Section: Soil Water Content (Swc)mentioning
confidence: 64%
“…As plants did not flower in our previous experiments (Wang et al 2005(Wang et al , 2007 we do not know whether seed yield is affected similarly as vegetative growth. In a crop as oilseed rape with an indeterminate growth habit in which the reproductive growth phase largely overlaps with the vegetative growth phase, these phases may respond differently to environmental conditions.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations